Fractionation of perfluoroalkyl acids (PFAAs) along the aquatic food chain promoted by competitive effects between longer and shorter chain PFAAs. (March 2023) - Wen, Wu; Xiao, Lu; Hu, Diexuan; Zhang, Zhining; Xiao, Yilin; Jiang, Xiaoman; Zhang, Shangwei; Xia, Xinghui
Abstract: Perfluoroalkyl acids (PFAAs) are proteinophilic pollutants. We hypothesized that fractionation of PFAAs may occur along a food chain. To testify this hypothesis, we investigated the bioconcentration, bioaccumulation, and fractionation of 11 kinds of PFAAs (C–F = 3–11) along an aquatic food chain consisting of D. magna, zebrafish, and cichlid. The results showed that the proportions of PFNA, PFOA, and all shorter chain PFAAs in the D. magna and fish tissues were lower than the ones in exposure water, opposing to the other longer chain PFAAs. Predation promoted such fractionation differences, and the proportions of PFNA, PFOA, and all shorter chain PFAAs in organisms decreased while those of the other longer chain PFAAs increased along the food chain. The results of isothermal titration calorimetry and molecular docking experiments showed that binding affinities of PFAAs and fish proteins increased with the number of perfluorinated carbons, resulting in a substitution of shorter chain PFAAs by their longer chain analogues. It also triggered the differences in the uptake and elimination of PFFAs and competitive bioaccumulation between longer and shorter chain PFAAs. This study suggests that fractionation should be considered in studying environmental behaviors and evaluating ecological risks of multiple PFAAs. Highlights: Fractionation was observed in D. magna and fish. Proportions of PFAAs increased with perfluorinated carbon number in organisms. Predation and food chain transfer promoted the fractionation. Binding affinities increased with perfluorinated carbon number. Shorter chain PFAAs were replaced by longer chain PFAAs on zL-FABP.